Dormant non-culturable Mycobacterium tuberculosis retains stable low-abundant mRNA - Ignatov, Dmitriy V. (BMC Genomics, 2015)
BACKGROUND: Dormant Mycobacterium tuberculosis bacilli are believed to play an important role in latent tuberculosis infection. Previously, we have demonstrated that cultivation of M. tuberculosis in K(+)-deficient medium resulted in generation of dormant cells. These bacilli were non-culturable on solid media (a key feature of dormant M. tuberculosis in vivo) and characterized by low metabolism and tolerance to anti-tuberculosis drugs. The dormant bacteria demonstrated a high potential to reactivation after K(+) reintroduction even after prolonged persistence under rifampicin. In this work, we studied the transcriptome and stability of transcripts in persisting dormant bacilli under arrest of mRNA de novo synthesis. RESULTS: RNA-seq-based analysis of the dormant non-culturable population obtained under rifampicin exposure revealed a 30–50-fold decrease of the total mRNA level, indicating global transcriptional repression. However, the analysis of persisting transcripts displayed a cohort of mRNA molecules coding for biosynthetic enzymes, proteins involved in adaptation and repair processes, detoxification, and control of transcription initiation. This ‘dormant transcriptome’ demonstrated considerable stability during M. tuberculosis persistence and mRNA de novo synthesis arrest. On the contrary, several small non-coding RNAs showed increased abundance on dormancy. Interestingly, M. tuberculosis entry into dormancy was accompanied by the cleavage of 23S ribosomal RNA at a specific point located outside the ribosome catalytic center. CONCLUSIONS: Dormant non-culturable M. tuberculosis bacilli are characterized by a global transcriptional repression. At the same time, the dormant bacilli retain low-abundant mRNAs, which are considerably stable during in vitro persistence, reflecting their readiness for translation upon early resuscitation steps. Increased abundance of non-coding RNAs on dormancy may indicate their role in the entry into and maintenance of M. tuberculosis dormant non-culturable state. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-015-2197-6) contains supplementary material, which is available to authorized users.